Faal Paru Dinamis: [Dynamic Lung Function] - Arief Bakhtiar; Renny Irviana Eka Tantri (Jurnal Respirasi, 2017)
Pulmonary function is an examination to measure lung volume function using spirometry. Tests with spirometry to detect abnormalities associated with respiratory distress. Spirometry examination is not only to determine the diagnosis but also to assess the severity of obstruction, restriction, and the effects of treatment. Spirometry examination is a test to measure the volume of a person’s static and dynamic lungs with a spirometer tool. Dynamic lung spirometry consists of Forced vital capacity (FVC), Forced expiratory volume (FEVT), Forced expiratory flow200-1200 / FEF 200-1200, Forced expiratory flow25% -75% / FEF 25% -75%, Peak expiratory flow rate / PEFR, Maximum voluntary ventilation / MVV / MBC, FEV1 / FVC Ratio. Ventilation disorders consist of: restriction and obstruction disorders. Restriction is a disorder of lung development by any cause. In obstruction disorder, it shows a decrease in velocity of expiratory flow and normal vital capacity. FEV values, which are widely used are FEV1 / FVC, abnormal when <80%, FEV1 / FVC ratio <80%. This parameter is very important because the accuracy level for obstruction in the central airway is quite large. In obstructive disorder there is generally a decrease in pulmonary dynamic volume. Significant parameters are FEV 1 / FVC, PEFR, and FEF 25-75. The FEV1 / FVC ratio is important because the accuracy level for obstruction in the central airway is considerable, whereas FEF 25-75 indicates obstruction in the small airway.